Palliative radiotherapy for gross hematuria in patients with advanced cancer - Mami Ogita (Nature Portfolio, 2021)
Abstract This study assessed the efficacy of palliative radiotherapy for gross hematuria caused by advanced cancer. Patients who received palliative radiotherapy to control gross hematuria in two hospitals between October 2006 and May 2020 were retrospectively reviewed. We evaluated the gross hematuria response, gross hematuria control duration, blood transfusion rate, blood transfusion-free duration, and overall survival. Cox multivariate analysis was performed to examine factors associated with hematuria control duration. Fifty-three consecutive patients were included. The most frequently used dose fractionation regimen was 30 Gy in 10 fractions (BED10 = 39 Gy), followed by 20 Gy in 5 fractions (BED10 = 20 Gy). Forty patients (76%) became gross hematuria free. The median hematuria control duration was 4.3 months (95% confidence interval 1.9–6.6). Twenty-six patients received blood transfusion 3 months before radiotherapy; 17 of them (65%) were free from blood transfusion 1 month after radiotherapy. A high BED10 (≥ 36 Gy) was a statistically significant factor for hematuria control duration in the multivariate analysis (P = 0.02). Palliative radiotherapy can effectively relieve gross hematuria irrespective of the primary tumor site. A high BED10 may be recommended for a prolonged hematuria control duration if patients have a good prognosis.